MODEL KEBIJAKAN PENGELOLAAN SUMBERDAYA KELAUTAN DALAM PERSPEKTIF RESOLUSI KONFLIK (Studi Kasus Nelayan Teluk Limau Bangka Barat Provinsi Kepulauan Bangka Belitung) - Aimie Sulaiman; Iskandar Zulkarnain; Yulian Fakhrurrozi (Environmental Research Center (PPLH) of Udayana University, 2015)
Research aimed at mapping the dynamics of conflict and conflict resolution, to analyzethe fishery potension and estates, as well as government policy areas West Bangka districtabout efforts to protect the marine ecosystem in Teluk Limau Kecamatan Parit Tiga threat ofdegradation. A policy in the mining sector that issued the draft local regulations which donot favor the interests of the community, a grass-roots rejection of Community fishermenharvest that ended in open conflict across the community. By applying the model of integrativepolicy approaches through conflict resolution, regulation which is accommodating andlocal wisdom-based ethnotechnology, development is expected to be sustainable economicdevelopment can be realized in the future.